Dinamika Program Penanggulangan Hiv dan Aids Di Komunitas (Studi Kasus : Proses Persiapan dan Implementasi Community Organizer Di Jakarta Utara) - Sugiarto, Edi; Machdum, Sari Viciawati (Jurnal Ilmu Kesejahteraan Sosial, 2015)
This research about community organizing heterogeneous in a geographic region on the issue of HIV and AIDS. The study was conducted for the prevention of HIV and AIDS has been made to key populations, individual and group (at the micro level). Research with qualitative approach and descriptive methods have found that it is not easy to organize geographic community with interven-tions on the mezzo level on the issue of HIV & AIDS with peculiarities in it. Community Organizer recruited not suitably qualified so the impact on their work. The role played not yet fully reflect the work processes at the level of mezzo, and practice their skills as social analysis, participation growth, regeneration, and the organization became not optimal